Comparative assessment of performance, combustion, and emission of compression ignition engine fuelled with different generations of biodiesel. Issue 6 (2nd November 2021) - Kumbhar, Vishal Sharad; Pandey, Anand; Varghese, Anil; Patil, Virendra
ABSTRACT: In the present research work, the performance, combustion and emission characteristics of compression ignition engine fuelled 22 different biodiesels categorised as (first, second, third generation, waste oil, and animal oil) biodiesel (B100) are evaluated numerically and compared with diesel fuel. Diesel-RK, a full-thermodynamic cycle engine analysis tool was used to carry out the numerical analysis. The engine power, fuel consumption, ignition delay, maximum cylinder pressure, oxides of nitrogen (NOx ), and carbon dioxide (CO2 ) emission were investigated at four different engine operating loads. Power output was observed to be higher for Corn oil biodiesel, while Jatropha oil biodiesel produced lower fuel consumption among all other biodiesel. 9.1% increase in-cylinder peak pressure was found for waste transformer oil biodiesel than diesel, while ignition delay was found to be lowest for Rapeseed oil BD, Rice bran oil BD among all other biodiesel. The NOx emissions were higher for biodiesel by 30–32%, while CO2 emissions were reduced by 10–12% compared to diesel. The physicochemical properties of biodiesel were responsible for the diverse characteristics of the engine.